2017
DOI: 10.1002/jqs.2927
|View full text |Cite
|
Sign up to set email alerts
|

Younger Dryas glaciers and climate in the Mourne Mountains, Northern Ireland

Abstract: Here, we present evidence to suggest that the Mourne Mountains, Northern Ireland, were last occupied by glaciers during the Younger Dryas Stadial. The margins of these glaciers are marked by moraines, chronologically constrained to the Younger Dryas by Schmidt hammer exposure dating. Reconstructions indicate that these glaciers had equilibrium‐line altitudes (ELAs) ranging from 356 ± 33 m (a.s.l.) to 570 ± 9 m (a.s.l.), with a mean of 475 ± 36 m (a.s.l.). ELAs rise from west to east, probably reflecting the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 137 publications
0
15
1
Order By: Relevance
“…To develop a deglacial chronology, sampling was focused on prominent moraines and boulder accumulations as these are the best geomorphological indicators of the dimensions of former mountain glaciers (Barr et al ., ). Key sites along the main SW–NE axis of the mountain range were targeted for SH exposure dating (SHED; Tomkins et al , ) including glacially deposited boulders on prominent cirque moraines (>400 m) at Kelly's Lough (KL), Lough Nahanagan (LN), Mullaghcleevaun (MC) and Upper Lough Bray (ULB).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…To develop a deglacial chronology, sampling was focused on prominent moraines and boulder accumulations as these are the best geomorphological indicators of the dimensions of former mountain glaciers (Barr et al ., ). Key sites along the main SW–NE axis of the mountain range were targeted for SH exposure dating (SHED; Tomkins et al , ) including glacially deposited boulders on prominent cirque moraines (>400 m) at Kelly's Lough (KL), Lough Nahanagan (LN), Mullaghcleevaun (MC) and Upper Lough Bray (ULB).…”
Section: Methodsmentioning
confidence: 97%
“…; Table ). Twenty surfaces were sampled at each site (Carrawaystick Brook; n = 10) and 170 surfaces were sampled in total, comparable to previous applications of SHED in the Mourne Mountains, Northern Ireland (Barr et al ., ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ballantyne and O Cofaigh, 2017), suggesting that these and possibly other mountains in north-west Ireland supported the last remnants of the last Irish Ice Sheet before complete disappearance of glacier ice under the warmer conditions of the Lateglacial Interstadial. The Blue Stack Mountains, along with other mountain areas in Ireland, hosted glaciers during the Younger Dryas Stadial ($12.9-11.7 ka) (Barr et al, 2017;Barth et al, 2018;Tomkins et al, 2018), but it has not yet been demonstrated that these glaciers had persisted throughout the Lateglacial Interstadial.…”
Section: Deglacial Chronology Of South Donegal and Donegal Baymentioning
confidence: 99%
“…In the case of discrete ice masses (corrie glaciers, valley glaciers and icefields) relating to the Younger Dryas (∼12.9-11.7 ka), geomorphological mapping has facilitated three-dimensional palaeoglaciological reconstructions and, in turn, calculations of palaeoclimatic variables (e.g. Ballantyne, 2002aBallantyne, , 2007aBallantyne, , 2007bBarr, Roberson, Flood, & Dortch, 2017;Bendle & Glasser, 2012;Benn & Ballantyne, 2005;Boston, Lukas, & Carr, 2015;Finlayson, Golledge, Bradwell, & Fabel, 2011;Lukas & Bradwell, 2010). Despite this large body of research, there remain several areas in Britain and Ireland where past glacial events remain poorly constrained, in large part due to the paucity of detailed geomorphological mapping in those areas.…”
Section: Introductionmentioning
confidence: 99%